Surgical approach of juvenile nasopharyngeal angiofibroma - Adham, Marlinda (Oto Rhino Laryngologica Indonesiana, 2022)
ABSTRACT  Background: Juvenile nasopharyngeal angiofibroma (JNA) is a histologically benign tumor of blood vessels but clinically malignant, with distinctive growth patterns, and required various surgical approaches. The tumor arises from superior posterior sphenopalatine foramen with nasal obstruction and recurrent epistaxis symptoms. Purpose: To discuss the best surgical approach regarding the JNA stage. Case Report:  A 13-year-old boy came complaining of recurrent unilateral epistaxis, unilateral nasal obstruction, and swelling of the right cheek. Tumor had expanded from nasopharynx to anterior maxillary region and intracranial. Clinical Question: Is open surgery with a lateral approach the best choice for clearing up the tumor mass and preventing recurrency in JNA which had expanded to anterior maxillary area and intracranial? Method: Literature search was conducted through PubMed, Clinical Key, Cochrane, and Google Scholar using keywords which were “juvenile nasopharyngeal angiofibroma”, “open surgery”, and “tumor recurrence”, obtained 71 papers which were screened using the inclusion and exclusion criteria. Result: The primary treatment for JNA is surgery, and the surgical approaches vary from anterior, lateral, and inferior. The literature search obtained one retrospective cohort study complied with this case, which reported 33 patients with JNA. Interventions on 25 patients with lateral surgical approaches and 8 patients with other approaches.  There were 3 patients with lateral approach intervention and 2 patients with other approaches, had JNA tumor recurrence.   Conclusion: The lateral approach is the best approach for clearing up the entire tumor mass and preventing recurrency in JNA cases with expansion to anterior maxillary region and intracranial. ABSTRAK  Latar Belakang: Angiofibroma nasofaring belia (ANB) adalah tumor pembuluh darah yang secara histologis jinak tetapi klinis ganas, dengan pola pertumbuhan beragam dan membutuhkan teknik pendekatan pembedahan yang berbeda. Tumor berasal dari area superoposterior foramen sfenopalatina, mempunyai gejala klinik berupa sumbatan hidung dan epistaksis berulang. Tujuan: Menentukan tatalaksana pendekatan terbaik pembedahan ANB sesuai perluasan tumor. Laporan Kasus: Pasien laki-laki berusia 13 tahun dengan keluhan epistaksis berulang dari hidung kanan, hidung tersumbat, dan bengkak di daerah pipi kanan. Tumor sudah meluas ke nasofaring sampai ke intrakranial.  Pertanyaan Klinis: Apakah pembedahan terbuka dengan pendekatan lateral merupakan pilihan terbaik untuk mengangkat seluruh massa tumor serta mencegah rekurensi, pada kasus ANB dengan perluasan ke area anterior maksila serta ke intrakranial? Metode: Pencarian literature menelusuri Pubmed, Clinical Key, Cochrane, dan Google Scholar menggunakan kata kunci “juvenile nasopharyngeal angiofibroma”, “open surgery”, dan “tumor recurrence” diperoleh 71 naskah yang selanjutnya disaring dengan kriteria inklusi dan eksklusi.  Hasil: Terapi utama ANB adalah pembedahan dengan arah pendekatan yang bervariasi tergantung dari lokasi massa tumor, yaitu pendekatan dari anterior, lateral, atau inferior. Dari pencarian literatur diperoleh satu penelitian retrospektif yang melaporkan 33 kasus ANB, dimana 25 kasus dilakukan intervensi pendekatan lateral dan 8 pasien dengan cara pendekatan lainnya, dan didapati   3 kasus dengan pendekatan lateral dan 2 kasus dengan pendekatan lain mengalami rekurensi. Kesimpulan: Pembedahan dengan pendekatan lateral merupakan cara pendekatan terbaik untuk mengangkat massa tumor sebersih mungkin dan mencegah terjadinya rekurensi pada kasus ANB dengan perluasan ke anterior maksila serta ke intrakranial.